Selected simple methods of plant cell wall histochemistry and staining for light microscopy - Soukup, Aleš (Methods in molecular biology, 2014)
Histochemical methods allow for identification and localization of various components within the tissue. Such information on the spatial heterogeneity is not available with biochemical methods. However, there is limitation of the specificity of such detection in context of complex tissue, which is important to consider, and interpretations of the results should regard suitable control treatments if possible. Hereby we present set of selected simple staining and histochemical methods with comments based on our laboratory experience.
Keywords: Histocytochemistry; Staining and Labeling; Plant Cells; rostlinné buňky; mikroskopie; Microscopy; buněčná stěna; histocytochemie; barvení a značení; Cell Wall